Experience in Validation of Methods for Determination of Radiochemical Impurities in Radiopharmaceuticals - A. O. Malysheva; G. E. Kodina; E. A. Lyamtseva; N. A. Taratonenkova; A. S. Lunev (Регуляторные исследования и экспертиза лекарственных средств, 2020)
Most important quality attributes of any radiopharmaceutical (RPh) are its radiochemical purity (RCP) or content of radiochemical impurities (RCIs) that have to comply with respective norms and limits. However, at present, there is no unified approach to validation of analytical methods in the context of highly radioactive samples.The aim of the study was to develop an approach to validation of methods for determination of RCI content in RPhs.Materials and methods: the authors determined the content of RCIs in a radiopharmaceutical formulation containing a complex of technetium-99m and methylenediphosphonic acid by the radiometric method after isolation of impurities from the main compound by thin-layer chromatography using silica gel and methyl ethyl ketone (for sodium pertechnetate determination) and silica gel and 13.6% sodium acetate solution (for determination of hydrolysed reduced technetium-99m). The radioactivity was registered by a chromatogram scanner with a detector of gamma-rays with energies from 0.05 to 1.5 MeV.Results: the paper analyses existing official approaches to validation of analytical procedures and compares them with the results of experimental studies described in available publications. It assesses the validation parameters for compliance with the acceptance criteria set forth in the current regulations and substantiates selectivity of chromatographic determination of impurities under the selected test conditions. Coefficients of variation for repeatability, reproducibility, and accuracy did not exceed 4.5, 2.8, and 8.9%, respectively, given the relative error of not more than 10.5%. The study demonstrated signal linearity for the 10-fold dilution of the standardised sodium pertechnetate solution, it also demonstrated correspondence between the applied and detected radioactivity when performing the test in the impurity content range of 0.5–5%. The validation procedure was associated with significant radiation burden for the personnel of the quality control laboratory.Conclusions: the authors suggested a methodological approach to validation of methods for determination of RCI content in technetium-99m-based RPhs. This approach may be used in the development of a guideline on validation of analytical methods for RCP/RCI determination in RPhs, or for introduction of relevant sections into existing documents.